Humoral and cellular immune responses after COVID-19 vaccination of lung transplant recipients and patients on the waiting list: a 6-month follow-up - Hoek, Rogier A. S.; Liu, Siqi; GeurtsvanKessel, Corine H.; Verschuuren, Erik A. M.; Vonk, Judith M.; Hellemons, Merel E.; Kool, Mirjam; Wijbenga, Nynke; Bogers, Susanne; Scherbeijn, Sandra; Rugebregt, Sharona; van Gemert, Johanna P.; et al. (Frontiers in Immunology, 2024)
BACKGROUND: Data on cellular response and the decay of antibodies and T-cells in time are scarce in Lung Transplant Recipients (LTR). Additionally, the development and durability of humoral and cellular immune responses has not been investigated in patients on the waitlist for lung transplantation (WL).Here, we report our six months follow-up of humoral and cellular immune responses of LTR and WL, compared to controls. METHODS: Humoral responses to two doses of the mRNA-1273 vaccination were assessed by determining Spike (S)-specific IgG antibodies and neutralizing antibodies. Cellular responses were investigated by Interferon gamma (IFN-γ) release assay (IGRA) and IFN-γ ELISpot assay at 28 days and 6 months after second vaccination. RESULTS In LTR, level of antibodies and T-cell responses were significantly lower at 28 days after the second vaccination. Also, WL had lower antibody titers and lower T-cell responses compared to controls. Six months after the second vaccination, all groups showed a decrease in antibody titers and in T-cell responses. In WL, the rate of decline of neutralizing antibodies and T-cell responses was significantly higher than in controls.CONCLUSIONS: Alternative: Our results show that humoral and cellular responses in LTR, if they develop, decrease at rates comparable to controls. In contrast, the inferior cellular responses and the rapid decay of both humoral and cellular responses in the WL groups implies that WL may not be protected adequately by two vaccinations and repeat boostering may be necessary to induce protection that lasts beyond the months immediately post-transplantation